2022
DOI: 10.1155/2022/1039393
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Profiles and Their Relevance with Temporomandibular Disorder Symptoms in Preorthodontic Patients

Abstract: Background. Temporomandibular disorders (TMDs) refer to a group of heterogenous musculoskeletal diseases with diverse clinical symptoms and an undetermined aetiology. The psychological profiles were closely related to the onset and treatment outcomes of TMDs. Objective. To examine the relevance between psychological profiles and different symptoms of TMDs in preorthodontic patients. Methods. The study was conducted among 570 preorthodontic patients. TMDs symptoms were recorded by the Diagnostic Criteria for TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…People with higher education levels might understand the questions better, or they may pay more attention to oral health issues. In addition, other studies have suggested that pain perception may be influenced by demographic‐social factors such as education level 40–42 . These are all possible causes of the above results.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…People with higher education levels might understand the questions better, or they may pay more attention to oral health issues. In addition, other studies have suggested that pain perception may be influenced by demographic‐social factors such as education level 40–42 . These are all possible causes of the above results.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, other studies have suggested that pain perception may be influenced by demographic-social factors such as education level. [40][41][42] These are all possible causes of the above results.…”
Section: Ta B L E 1 Descriptive Analyses Of the Datamentioning
confidence: 89%
“…Four of them indicated significant positive low correlation between TMD and anxiety. 15 , 16 , 19 , 21 One study in the US reported significant positive low correlation between chronic orofacial pain and anxiety. 17 The diagnosis of chronic orofacial pain being included in that study includes trigeminal neuralgia (51.5%), other neuropathic diagnoses (14.6%), persistent idiopathic orofacial pain (5.3%), and other diagnoses.…”
Section: Resultsmentioning
confidence: 99%
“…Estrogen metabolism might also greatly contribute to the osseous changes of the condyle and enhance pain sensibility [ 35 , 36 ]. As they are closely related to abnormal oral parafunctions such as grinding and clinching, or sleep disorders, some psychological and social indicators might be unneglectable topics in studying these differences [ 37 ]. In this study, sex-related morphological changes in DD were significant.…”
Section: Discussionmentioning
confidence: 99%